2018
DOI: 10.1080/15568318.2017.1368748
|View full text |Cite
|
Sign up to set email alerts
|

Estimating individual physical capability (IPC) to make journeys by bicycle

Abstract: We propose a novel method to estimate capability to make bicycle journeys, specifically considering the individual physical capability (IPC) of entire populations of individuals from all population segments of an area, not just current cyclists. IPC considers the physical constraints on the maximum distance people could cycle given the typical topography of where they live (Distance IPC), and then estimates their ability to make a particular journey (Journey IPC). IPC, when estimated in this way for a particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Subsequent work by Philips et al [23,24] has shown that, if hilliness is defined according to the slope of roads within an area, 8% of the population in England live in small areas (LSOAs-Lower Super Output Areas-The areal units defined for analysing the UK Census) where the roads in their locale are predominantly over 4%, and many more will live in areas where at least some of the roads are this steep, meaning that many potential cyclists will be affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subsequent work by Philips et al [23,24] has shown that, if hilliness is defined according to the slope of roads within an area, 8% of the population in England live in small areas (LSOAs-Lower Super Output Areas-The areal units defined for analysing the UK Census) where the roads in their locale are predominantly over 4%, and many more will live in areas where at least some of the roads are this steep, meaning that many potential cyclists will be affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…E-bikes in particular have significant substitution potential, some call them a 'game changer', as e-bikers have been found to take longer trips by e-bike and bicycle, compared to cyclists, with larger potential for mode substitution away from cars (Castro et al, 2019, Mason et al, 2015, Kroesen, 2017. It has been estimated that e-bikes, if used to replace car travel, have the 'physical capability' (simulated as how far people are capable of travelling) to cut car CO2 emissions in England by up to 50% (about 30 million tonnes per year) (Philips et al, 2018, Philips et al, 2020. The greatest opportunities were found to be in rural and sub-urban settings: city dwellers already have many low-carbon travel options, so the greatest impact would be on encouraging e-bike use outside urban areas.…”
Section: Empirical Work: Cross-sectional and Longitudinalmentioning
confidence: 99%
“…: leisure destinations, healthcare services) to capture different needs and behavior. Further studies could also build on this methodology to model the cost coefficient as a function of socio-demographic and behavioral variables, in order to be able to subsequently apply it to the general population, as done in a recent study assessing the physical capability to travel by bicycle (Philips, Watling, & Timms, 2018). The choice of the thresholds also entails equity implications.…”
Section: Spatial Analysis Across Boroughsmentioning
confidence: 99%